The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1ra00254f
|View full text |Cite
|
Sign up to set email alerts
|

Novel sustainable materials from waste plastics: compatibilized blend from discarded bale wrap and plastic bottles

Abstract: This work studies a novel sustainable polymeric material made from a reactive blend of two agri-food waste plastics, with the new material showing strong promise for value-added industrial uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…The incorporation of a compatibilizer in a melt‐process might be useful for improving the effectiveness and enhancement of the properties of rPET/rLDPE blends. Recently, Gupta et al [ 64 ] has demonstrated the blends of rPET and recycled linear low‐density polyethylene (rLLDPE) with linear triblock copolymer of styrene (30%) and SEBS with 1.0–1.7% maleic anhydride grafted onto the rubber midblock (Kraton) as a compatibilizer and styrene–acrylic–glycidyl methacrylate (Joncryl) as a chain extender. It was found that the impact resistance and elongation at break of the developed blend were placed in the range of a packaging material and was also suitable for production of filaments for 3D printing.…”
Section: Blending and Compatibilizationmentioning
confidence: 99%
“…The incorporation of a compatibilizer in a melt‐process might be useful for improving the effectiveness and enhancement of the properties of rPET/rLDPE blends. Recently, Gupta et al [ 64 ] has demonstrated the blends of rPET and recycled linear low‐density polyethylene (rLLDPE) with linear triblock copolymer of styrene (30%) and SEBS with 1.0–1.7% maleic anhydride grafted onto the rubber midblock (Kraton) as a compatibilizer and styrene–acrylic–glycidyl methacrylate (Joncryl) as a chain extender. It was found that the impact resistance and elongation at break of the developed blend were placed in the range of a packaging material and was also suitable for production of filaments for 3D printing.…”
Section: Blending and Compatibilizationmentioning
confidence: 99%
“…5c showed the integral surface under the mechanical curve of the mixture, i.e. the tensile strength (τ) calculated according to Equation (7). :…”
Section: Mechanical Properties and Microtopographymentioning
confidence: 99%
“…Recycling is a logical choice for plastic waste disposal. However, plastics are contaminated during use, due to presence of additives and mixtures in plastics, and hence performance degradation during recycling process make recycling expensive and unattractive [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve a uniform phase morphology, the application of compatibilizers and surface treatment of nanoparticles suggested previously in some studies 11,12 is not admired in the latest studies due to dire implications on sustainability and cost-effectiveness of the fabrication process. [13][14][15] To the best of our knowledge, there is no study available based on the combination of non-compatibilized HDPE polymer and non-treated hybrid bentonite nano clay with CaCO 3. Therefore, the objective of this work is to investigate the influence of non-compatibilized HDPE polymer matrix and non-surface treated hybrid reinforcements (CaCO 3 particles and bentonite nano clay as secondary reinforcements) on the wear and friction behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a uniform phase morphology is paramount for enhanced tribological properties. To achieve a uniform phase morphology, the application of compatibilizers and surface treatment of nanoparticles suggested previously in some studies 11,12 is not admired in the latest studies due to dire implications on sustainability and cost‐effectiveness of the fabrication process 13–15 …”
Section: Introductionmentioning
confidence: 99%